Concept of Civilizational Matrix in the Macrosociological Analisys of Social Changes - Pogosyan, Vardges (Journal of Sociology: Bulletin of Yerevan University, 2015)
The article analyzes the main provisions of the idea of the civilizational matrix in terms of applicability in the analysis of social change. Affirming that the conservation of integrative qualities of the system after the passage of the bifurcation points in their development is conditioned by a complex of stable socio-cultural constants, components of the civilizational matrix; social modernization in this case acts as an adequate protective response to changing environmental conditions, a means of maintaining relative homeostasis system status.